Pengaruh Kualitas Pelayanan, Pemahaman Wajib Pajak, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Pada Wajib Pajak Orang Pribadi di Wilayah Sunter, Jakarta Utara - Ayu Atmanti, Maria Maurin; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
This study aims to examine the effect of service quality, understanding of taxpayers, and tax sanctions on taxpayer compliance. This research was conducted in the Sunter area of North Jakarta with the Convenience Sampling method using primary data. This research is a quantitative approach by processing questionnaire data using multiple regression analysis methods. The population in this study are individual taxpayers who are in the Sunter area of North Jakarta so that a sample of 100 respondents is obtained. The results “of this study indicate that the understanding of taxpayers and tax sanctions have a positive effect on taxpayer compliance, and service quality has no effect on taxpayer compliance.”